2018
DOI: 10.1002/bio.3482
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and luminescence properties of novel 8‐hydroxyquinoline derivatives and their Eu(III) complexes

Abstract: Six novel 8-hydroxyquinoline derivatives were synthesized using 2-methyl-8-hydroxyquinoline and para-substituted phenol as the main starting materials, and were characterized by H nuclear magnetic resonance (NMR), mass spectrometry (MS), ultraviolet (UV) light analysis and infra-red (IR) light analysis. Their complexes with Eu(III) were also prepared and characterized by elemental analysis, molar conductivity, UV light analysis, IR light analysis, and thermogravimetric-differential thermal analysis (TG-DTA). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To our delight, when AgOTf decreased to 0.5 mol%, a parallel yield was also observed (entry 14-16). Solvent and temperature optimization revealed that other medias are not suitable in terms of yield comparable to that in DCE at 80 C (entry [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our delight, when AgOTf decreased to 0.5 mol%, a parallel yield was also observed (entry 14-16). Solvent and temperature optimization revealed that other medias are not suitable in terms of yield comparable to that in DCE at 80 C (entry [17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Moreover, 8hydroxyquinolines have been gaining attention in metallocene complex catalyzed transformations, in which they are utilized as effective multidentate ligands. [10][11][12][13][14][15][16][17][18][19][20][21] In view of the remarkable importance of this class of heterocyclic compounds, the eld of 8-hydroxyquinoline synthesis is continuously gaining attention. Although 8-hydroxyquinolines could be prepared by hydrolysis of 8-haloquinolines 22 or 8-aminoquinolines, 23 the latter two quinolone derivatives were not easily accessible.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of relative fluorescence quantum yields has exclusively been done by optical methods, most prominently using a spectrofluorometer and the comparative method as proposed by Parker and Rees. 25 In this paper, the ɸ f was calculated by a comparative method using the following equation 6,26,27 Φ Φ . .…”
Section: Methodsmentioning
confidence: 99%
“…The addition of substituents at the C-2 position of the pyridine ring, such as in ligands 1b, 1c, 1g, 1i, 1l, 1n, 1o, 1p, 1q, and 1r (Table 5, entries [3][4][5][6][7][8][9][10][11], results in a certain spatial steric resistance to the complex structure, which was not conducive to the formation of a stable five-membered ring structure. If electron-donating groups were introduced at ortho positions, the distribution of the electron cloud would change, which might significantly alter the LUMO value and expand the HOMO and LUMO gaps, such as in the zinc, cadmium, and aluminum complexes 1o, 1p, and 1q (Table 7), which resulted in a significant blue shift of the fluorescence emission wavelength.…”
Section: Analysis Of the Effect Of The Structure On The Fluorescence Properties In Terms Of Molecular Orbitalsmentioning
confidence: 99%
See 1 more Smart Citation